No-place, new places: Death and its rituals in urban Asia - KONG, Lily (Institutional Knowledge at Singapore Management University, 2017)
In many Asian cities, particularly those that confront increasing land scarcity, the conversion from burial to cremation has been encouraged by state agencies in the last several decades. From Hong Kong to Seoul to Singapore, planning agencies have sought to reduce the use of space for the dead, in order to release land for the use of the living. More secular guiding principles regarding efficient land use in these cities had originally come up against the symbolic values invested in burial spaces, resulting in conflicts between different value systems. In more recent years, however, the shift to cremation and columbaria has been marked and even voluntary. In still more recent years, even columbaria have become overcrowded, and sea burials (the scattering of ashes in the seas) are being encouraged, as are woodland burials (the scattering of ashes in woodlands or around trees) in places like Hong Kong and Taipei. Indeed, the latter has been promoted as the “new eco-friendly burial method.” As burial methods change, so too do commemorative rituals, and the annual Qingming Festival (tomb sweeping) has seen the rise of new online and mobile phone rituals in China. This paper traces the ways in which physical spaces for the dead in several Asian cities have diminished and changed over time, the growth of virtual space for them, the accompanying discourses that influence these dynamics, and the new rituals that emerge concomitantly with the contraction of land space.